INTERCULTURAL COMMUNICATION AMONG COWORKERS IN A MULTINATIONAL COMPANY: A PHENOMENOLOGICAL STUDY - David Randy (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This phenomenological study studies the intercultural communication of non-native English speaking professionals working in multinational companies in the UK to form the basis of comparison with their native English speaking counterparts. In this study, five native English speaking professionals currently working in England were interviewed. Respondents drew pictures to depict their professional and cultural experiences through interactions with non-English speaking colleagues. This study interacts on expected cross-cultural interactions or expectations and any miscommunications that may occur. Most of the respondents interacted positively between their cultures and shared their vocal and communication challenges. To overcome their challenge, all respondents admitted to speaking late or asked some confirmation questions such as "Do you need further explanation?" or "Is there anything you want to ask?" to reduce the possibility of conflict and miscommunication. However, all respondents agreed that there was a potential for unwanted harm and it was close to offending to occur. Based on the results, all respondents claimed to have good intentions in their actions but lack the skills to better facilitate communication with their non-native English speaking counterparts.